1968
DOI: 10.1121/1.1911056
|View full text |Cite
|
Sign up to set email alerts
|

Recognition Performance as a Function of Detection Criterion in a Simultaneous Detection-Recognition Task

Abstract: On each trial, one of three stimulus events occurred: Presentation of (1) a 500-cps signal added to a sample of white noise; (2) an 1100-cps signal added to the noise; or (3) no signal added to the noise. In the detection-recognition condition, each listener reported whether a signal occurred (detection) and which of the two signals it was (recognition). The listeners' criteria for a YES response were manipulated through instructions. The functions of primary concern were those relating the proportion of corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
12
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 0 publications
7
12
1
Order By: Relevance
“…This proposition follows directly from the basic tenets of signal detection theory and other continuous models of detection (Green & Swets, 1966). Threshold models of detection, however, in particular, high-threshold theory (Blackwell, 1963) and two-state low-threshold theory (Luce, 1963b), predict that recognition responses emitted in "nondetect" states should be distributed randomly among stimuli, and thus that recognition performance should be no better than chance when subjects report that no stimulus was presented (Lindner, 1968;Rollman & Nachmias, 1972). Our results are clearly to the contrary.…”
Section: F~tor'contrasting
confidence: 55%
“…This proposition follows directly from the basic tenets of signal detection theory and other continuous models of detection (Green & Swets, 1966). Threshold models of detection, however, in particular, high-threshold theory (Blackwell, 1963) and two-state low-threshold theory (Luce, 1963b), predict that recognition responses emitted in "nondetect" states should be distributed randomly among stimuli, and thus that recognition performance should be no better than chance when subjects report that no stimulus was presented (Lindner, 1968;Rollman & Nachmias, 1972). Our results are clearly to the contrary.…”
Section: F~tor'contrasting
confidence: 55%
“…She found reasonable support for a threshold-type model. Lindner (1968) examined a situation similar to Shipley's, but found that a threshold-type model did not fit his data. In particular, he found that the probability of a correct modality judgment, conditional upon a "no" detection response, was above the guessing level, contrary to the predictions of a simple threshold model.…”
Section: Resultsmentioning
confidence: 98%
“…We propose perhaps the simplest possible model for this situation. This model is a threshold-type model which is similar to those discussed by Shipley (1965) and Lindner (1968). We assume attention has no effect.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is not clear whether signals must always be recognized in order to be detected. Shipley (1965) argues from the results of her simultaneous detection and recognition experiment that this is true, but Lindner's (1968) data from a similar experiment do not support such a hypothesis. Macmillan (1971) presented evidence of a different sort that the detection of signals was not completely dependent on their recognition.…”
mentioning
confidence: 91%